2018
DOI: 10.7556/jaoa.2018.098
|View full text |Cite
|
Sign up to set email alerts
|

Medical Students’ Knowledge, Attitudes, and Behaviors With Regard to Skin Cancer and Sun-Protective Behaviors

Abstract: Physicians are uniquely positioned to counsel patients regarding sun-protective behaviors. Thus, a medical school curriculum that includes education about the sun's effect on health is needed for the prevention and early recognition of skin cancer in future patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 28 publications
(23 reference statements)
2
16
0
Order By: Relevance
“…The above‐mentioned deficits among outdoor workers are not surprising, considering similar findings were even observed among medical professionals. Though medical professionals were found to have slightly better knowledge in comparison to previous studies, they still showed a lack of knowledge and SPB . Thus, the necessary information transmission and elucidation has not yet been fully achieved.…”
Section: Discussionmentioning
confidence: 59%
See 4 more Smart Citations
“…The above‐mentioned deficits among outdoor workers are not surprising, considering similar findings were even observed among medical professionals. Though medical professionals were found to have slightly better knowledge in comparison to previous studies, they still showed a lack of knowledge and SPB . Thus, the necessary information transmission and elucidation has not yet been fully achieved.…”
Section: Discussionmentioning
confidence: 59%
“…Most medical professionals were aware of the harmful effects of UVR in relation to skin cancer . Isvy et al .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations